2017
DOI: 10.1371/journal.pone.0179852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the p53–tristetraprolin–stathmin-1 pathway on trophoblasts at maternal–fetal interface

Abstract: ProblemTo reveal the effect of p53–tristetraprolin–stathmin-1 signaling on trophoblasts and recurrent spontaneous abortion (RSA).Method of studyStathmin-1 (STMN1), p53, and tristetraprolin (TTP) expression in paraffin-embedded villus tissue was determined using immunohistochemistry. HTR-8/SVneo cells were treated with doxorubicin to activate p53; STMN1 and TTP levels were detected by quantitative reverse transcription–PCR and western blotting. Western blotting and immunofluorescence were used to investigate ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“… 24 Recently, we reported TTP expression is increased in trophoblasts from patients with RM compared to healthy controls. 25 Moreover, Kasra Khalaj et al. 26 showed that TTP protein was downregulated in an LPS-induced mouse pregnancy loss model, and its targets TNF-α and interleukin-6 (IL-6) were upregulated.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Recently, we reported TTP expression is increased in trophoblasts from patients with RM compared to healthy controls. 25 Moreover, Kasra Khalaj et al. 26 showed that TTP protein was downregulated in an LPS-induced mouse pregnancy loss model, and its targets TNF-α and interleukin-6 (IL-6) were upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1, as a cell proliferation promoter, has been confirmed in different types of cancers [ 26 ]. Additionally, the strong and widespread roles of p53 and p21 in regulating cell invasion and proliferation in several types of cancers and trophoblasts have been confirmed, and cervical cancer cells modified by PRDM4 show similar biological behavior [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Placental apoptosis is aggravated in placentas obtained from pregnancies with preeclampsia; this finding is associated with upregulation of p53, a well-studied tumor suppressor. Several studies have confirmed that suppression of P53 signal reduces both early and late trophoblast apoptosis, 25,26 and subsequently alleviate preeclampsia induced by trophoblast. In this study, we confirmed for the first time that TRIM72, which is overexpressed after treatment of CVMSCs-derived exosomes, can bind to P53 and promote P53 degradation in consistency with the previous report, and after P53 expression is reduced, the apoptosis rate of trophoblast is also decreased.…”
Section: Trim72 Regulates Trophoblast Proliferation Migration Invasio...mentioning
confidence: 92%